2012
DOI: 10.1521/jscp.2012.31.8.810
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Longitudinal Relation Between Loneliness and Depressive Symptoms: Prospective Effects and the Intervening Role of Coping

Abstract: loneliness and depressive symptoms are closely related constructs. however, mixed evidence exists on their prospective associations and only very few studies to date focused on intervening mechanisms. the present manuscript examined the direction of effects between loneliness and depressive symptoms in two longitudinal studies sampling college students (N = 514 and N = 437, respectively), using cross-lagged path analysis. Furthermore, the mediating and moderating role of active and passive coping strategies wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 57 publications
6
59
0
Order By: Relevance
“…Although not typically examined in a single study, a few investigations with adults (e.g., Aldwin & Revenson, 1987) and university students (e.g., Littleton et al, 2011) have found evidence for one directional pathway, but not the reverse (e.g., Vanhalst et al, 2012). Transactional associations could emerge only at specific times and for specific types of stressors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not typically examined in a single study, a few investigations with adults (e.g., Aldwin & Revenson, 1987) and university students (e.g., Littleton et al, 2011) have found evidence for one directional pathway, but not the reverse (e.g., Vanhalst et al, 2012). Transactional associations could emerge only at specific times and for specific types of stressors.…”
Section: Discussionmentioning
confidence: 99%
“…In a second longitudinal study (Calvete et al, 2011) of social stressors, coping, and adjustment among adolescents age 14 to 18 years, primary control coping (including problem solving, emotion regulation, and emotion expression) and disengagement coping were associated with symptom increases over time (see also Connor-Smith, Compas, Wadsworth, Thomsen, & Saltzman, 2000;Wadsworth, Raviv, Compas, & Connor-Smith, 2005). Finally, in a 6-month longitudinal study of 437 university students (Vanhalst et al, 2012), passive coping was associated with increased depression over time.…”
Section: Transactional Associations Between Emotional Sensitivity Andmentioning
confidence: 96%
See 1 more Smart Citation
“…The infrequent use of these specific strategies may be positive in that both have been associated with less desirable outcomes in prior research. Adapt is a form of avoidant coping that can be less helpful for relieving distress than active coping (e.g., Marroquín, Fontes, Scilletta, & Miranda, 2009;Martin, Wolter, Klaas, & Wood, 2010;Vanhalst, Luyckx, Teppers, & Goossens, 2012). Promotion of mistrust has been associated with negative child outcomes (Grindal & Nieri, 2015a, 2015b.…”
Section: Profiles Of Ers Strategiesmentioning
confidence: 99%
“…The results of some longitudinal studies carried out on non-clinical populations suggest that while loneliness and depression are mutually dependent in time, the impact of the sense of loneliness on depressive symptoms is greater (Vanhalst, Klimstra, et al, 2012) and more stable (Vanhalst, Luyckx, Teppers, & Goossens, 2012) than that of depression on loneliness.…”
Section: Introductionmentioning
confidence: 99%